2019
DOI: 10.1016/j.jsxm.2019.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Follow-Up After Penile Prosthesis Implantation—Survival and Quality of Life Outcomes

Abstract: Introduction Hydraulic penile prostheses have shown an overall good mechanical reliability up to 10 years after surgery; however, few data have been published on very long-term follow-up. Aim We looked at long-term (≥15 years) complications, including functional and quality of life (QoL) outcomes, after 3-piece inflatable penile prosthesis (IPP) implantation in patients with erectile dysfunction (ED). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 15 publications
4
33
1
Order By: Relevance
“…There are many studies in the literature that evaluate QoL of male patients with penile prostheses, but findings evaluating QoL of female partners could not be observed in these studies (8,22,23). In this study, partners' QoL was not at a healthy level before PPI.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…There are many studies in the literature that evaluate QoL of male patients with penile prostheses, but findings evaluating QoL of female partners could not be observed in these studies (8,22,23). In this study, partners' QoL was not at a healthy level before PPI.…”
Section: Discussionmentioning
confidence: 59%
“…Ure et al evaluated patients' QoL with SF 36 scale and observed that it was significantly increased after PPI compared to the preoperative period (7). However, in studies about patient QoL who underwent PPI, partner QoL was not mentioned much (8). In the current study, patients that did not respond to first-line and second-line treatments, and therefore underwent two-piece PPI were evaluated.…”
Section: Original Papermentioning
confidence: 86%
See 1 more Smart Citation
“…Annual IPP implantation cases rose in the US from 17,540 in 2000 to 22,420 in 2009, and the numbers continue to climb (7). Improvements in prosthetic design and surgical implantation techniques have resulted in longer device functional capacity and quality of life scores among patients, making this procedure popular and increasingly common (8). Still, post-operative pain continues to be a significant issue among patients undergoing IPP surgery, effecting up to 11.9% of patients at 5-year follow-up (9).…”
Section: Introductionmentioning
confidence: 99%
“…Long term function of the prosthesis, i.e., for up to 15 years along with the outcome of post-hospital syndrome have been investigated in past studies (12), (13). However, the mortality rate of patients based on the risks imposed by anaesthesia, along with the risks involved during the perioperative period has not been extensively studied by past literature (10).…”
Section: Introductionmentioning
confidence: 99%